Pengaruh Analisis Kebutuhan Pelatihan Budaya Keamanan Siber Sebagai Upaya Pengembangan Kompetensi bagi Aparatur Sipil Negara di Era Digital - Sri Cahaya Khoironi (BPSDMP Kominfo Jakarta, 2020)
The results of Monitoring and Evaluation of Electronic-Based Government Systems (SPBE) that not been optimal, the high incidence of cyber in the government domain. go.id due to system vulnerability as well as the number of government pages with unsafe conditions and not in accordance with existing international standards, show the need for ASN as a manager of digital competence to oversee digitalization in the government environment. To discuss this issue, the method chosen was the study of literature, by reviewing various literature and collection of research results in accordance with the problem. Descriptive qualitative analysis using the technique